PERBEDAAN STATUS KESEHATAN ORAL ANTARA PASIEN LANSIA PENYANDANG DIABETES MELLITUS TIPE 2 TIDAK TERKONTROL DENGAN PASIEN LANSIA BUKAN PENYANDANG DIABETES MELLITUS - , NOVI YATRI PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Diabetes mellitus (DM) type 2 is a hyperglycemic metabolic disease which happened because of insulin disfunction. The disease can be predominantly found in elders. Uncontrolled DM type 2 affects oral health status of the sufferers. Dry mouth, decayed, missing teeth, and periodontal disease are oral manifestations of uncontrolled DM type 2. The aim of this study was to determine is there any differences of oral health status between elders with uncontrolled DM type 2 and those without DM. This study was a descriptive epidemiology study with cross sectional approach. Subjects of this study were 40 elders with uncontrolled DM type 2 and 40 elders without DM, that lived in Daerah Istimewa Yogyakarta. Oral health status measured in each group consisted of OHI, DMF-T, PI, and GI. Data then were analyzed using non-parametric Mann-Whitney test. The result showed that oral health status of elders with uncontrolled DM type 2 (OHI = 2.02